PENGEMBANGAN BAHAN AJAR AKUNTANSI MATERI JURNAL PENYESUAIAN MENGGUNAKAN SOFTWARE EXE SEBAGAI SARANA SISWA BELAJAR MANDIRI KELAS XI IPS SMA NEGERI 7 SURAKARTA TAHUN AJARAN 2014/2015 - Mawarni, Anitah Diah; Adi, Wahyu; Sumaryati, Sri (Tata Arta, 2015)
ABSTRAK Tujuan penelitian ini adalah untuk mengetahui prosedur pengembangan bahan ajar akuntansi materi jurnal penyesuaian menggunakan software eXe dan menghasilkan bahan ajar akuntansi materi jurnal penyesuaian dari pengembangan software eXe yang layak digunakan di SMA Negeri 7 SurakartaPenelitian ini merupakan penelitian pengembangan (research and development).Penellitian pengembangan dilakukan di kelas XI IPS SMA Negeri 7 Surakarta.Model pengembangan menggunakan prosedural deskriptif dengan mengadopsi model penelitian pengembangan Borg & Gall.Metode yang digunakan dalam pengumpulan data yaitu observasi, wawancara dan kuisioner. Metode yang digunakan untuk menganalisis data adalah dengan teknik analisis deskriptif kuantitatif yang diungkapkan dalam distribusi skor skala lima terhadap kategori skala peniliaian yang telah ditentukan.Hasil penelitian menunjukkan bahwa uji coba ahli materi mendapatkan nilai 4,25 yang diinterpretasikan sangat baik. Uji coba ahli media mendapatkan nilai 4,91 yang diinterpretasikan sangat baik. Uji coba skala kecil mendapatkan nilai 3,9 yang diinterpretasikan baik. Uji coba skala besar mendapatkan nilai 4,23 yang diinterpretasikan sangat baikSimpulan dari penelitian ini adalah prosedur pengembangan bahan ajar akuntansi materi jurnal penyesuaian dengan menggunakan software eXe sebagai sarana siswa belajar mandiri siswa telah sesuai dengan prosedur pengembangan Borg & Gall dan Bahan ajar akuntansi materi jurnal penyesuaian dengan menggunakan software eXe layak diterapkan sebagai sarana siswa belajar mandiriKata kunci : Teknologi Pembelajaran, Pembelajaran Berbasis Komputer, Belajar Mandiri ABSTRACT  The demands in the era of globalization requires that students learn quickly, effectively and efficiently. Therefore, we need a technology that can be applied to support learning. One of the components that need to be considered in learning is learning materials. In creating effective learning, teachers need to design teaching materials of interest, relevant to the learning objectives and can increase student interest in learning. The objectives of this research are to investigate the procedure of development of interactive Accounting learning material on the topic of discussion of Journal Adjustment using the software of eXe and to produce a feasible interactive Accounting learning material on the topic of discussion of Journal Adjustment resulting from the development of eXe at State Senior Secondary School 7 of Surakarta.This research used the research and development (R&D) method. The development model used the procedural and descriptive one by adopting the research model claimed by Borg & Gall. The data of research were collected through observation, in-depth interview, and questionnaire. They were analyzed by using the descriptive quantitative one expressed in the score distribution of Scale 5 with the determined score scale categories. The result of research shows that the score of product testing by the expert of learning material and the expert of learning media is 4.25 interpreted as the very good one and 4.91 an interpreted as the good one too respectively. The score of the small scale testing was 3.9 interpreted as the good one whereas that of the large scale testing was 4.23 interpreted as the very good one respectively. Thus, the procedure of the development of development of interactive Accounting learning material on the topic of discussion of Journal Adjustment using the software of eXe as a means of autonomous learning of the students in Grade XI of Social Science Program of State Senior Secondary School 7 of Surakarta has been compliant with the procedure of development claimed by Borg & Gall, and such a developed Accounting learning material is feasible to be applied at State Senior Secondary School 7 of Surakarta as a means of having autonomous learning for the students.Keywords: Learning technology, Computer Assisted Instruction, Self Directed Learning